High gravity enzymatic hydrolysis of non–gelatinized starch from black - purple rice - Huong Do Thi Thanh; Thanh Nguyen, Tien (Vietnam Journal of Science and Technology, 2023)
Thanks to novel recombinant starch degrading enzymes which can directly hydrolyze raw starch at ambient temperature, the technology of hydrolysis of uncooked starch has recently been developed andproven to be effective. In combination with high substrate concentration (high gravity) approach, this technology not only saves the thermal energy for starch gelatinization but also reduces the impact of heat on valuable components in starch–containing raw materials. Black–purple rice is a specialty of Northwest Viet Nam, which contains high level of anthocyanin, a biologically active ingredient. In this study, commercial enzymes were applied to hydrolyze non–gelatinized black–purple rice to obtain anthocyanin–containing sugar solution. Factors affecting the starch conversion such as enzyme/substrate ratio, hydrolysis duration, temperature, and the presence of supporting enzymes in the hydrolysis process were investigated. The results showed that in the presence of Stargen 002, Viscozyme L, and Cellulast 1.5 L, more than 86 % of starch in a total of 320 g/L black-purple rice were converted into glucose after 72 hours at 50 °C. From black-purple rice, two products were received, including a glucose–rich hydrolysate (245.92 g/L) containing anthocyanin (30 mg/L) and a solid by–product rich in protein, which were very potential for food application.